Enhancing MSME Performance through Market Sensing Capability, Innovation Capability, and Iconic Ethnic Product Development - Latifah Anom; Abdul Azis Safii (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
Facing competition from global batik producers with prices that tend to be cheaper, MSME Batik Jonegoroan faces serious problems in its sales performance. This study aims to analyze the development of comparative product advantages sourced from the company's market sensing and innovation capabilities. Products with comparative advantage based on regional ethnic characteristics are expected to reclaim market share from Jonegoroan Batik. A total of 194 owners of SMEs producing Jonegoroan batik were sampled in this study. Structural equation modelling analysis with smart-PLS software shows that market sensing capability, innovation capability, and iconic ethnic product positively affect MSME performance. The indirect effect test proves that iconic ethnic products perform a mediating function in the relationship innovation capability and MSME performance. Meanwhile, the iconic ethnic product is not a mediating variable for the influence of market sensing capability on MSME performance. This finding implies that MSMEs with innovation capabilities should emphasise the orientation of developing comparative advantages of products based on ethnic characteristics to increase innovation and ultimately achieve company performance. The research limitation is related to data collection, which only involves one of the many MSME sectors that may affect the generalization of the research results.